2020
DOI: 10.3390/ijerph17186882
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Specific Warm-up during Bench Press and Squat Exercises: A Novel Approach

Abstract: The current study aims to verify the effects of three specific warm-ups on squat and bench press resistance training. Forty resistance-trained males (19–30 years) performed 3 × 6 repetitions with 80% of maximal dynamic strength (designated as training load) after one of the following warm-ups (48 h between): (i) 2 × 6 repetitions with 40% and 80% of the training load (WU), (ii) 6 × 80% of training load (WU80), or (iii) 6 × 40% of the training load (WU40). Mean propulsive velocity (MPV), velocity loss (VL), pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Similar to Ribeiro and colleagues, [21] Minas and collaborators [24] evaluated a specific warm-up in their study. These authors, although also used the squat exercise in their study, used two different warm-ups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to Ribeiro and colleagues, [21] Minas and collaborators [24] evaluated a specific warm-up in their study. These authors, although also used the squat exercise in their study, used two different warm-ups.…”
Section: Discussionmentioning
confidence: 85%
“…Otherwise, Ribeiro and colleagues, [21] aimed to understand the best intensity to use when only a specific warm-up was performed. This study verified if three types of warm-ups would have an effect on strength training, and its protocols would use three types of external loads in the warm-up exercise: 40% of the training load, 80% of the training load, and the combination of the 40% and 80% of the training load.…”
Section: Discussionmentioning
confidence: 99%
“…A study that evaluated the influence of specific warm-up on strength performance, found that participants were able to achieve a higher propulsive speed in the second and third sets in the squat, and with a tendency to decrease propulsive speed in the bench press, and the time for propulsive speed was shorter after warming up with progressive intensity, demonstrating that speed can be affected by warming up, tending to decrease with more activities [29]. In the horizontal bench press, the MPV does not tend to be greater at the beginning of the training, this is explained by the lower muscle mass involved, when compared to other exercises, in addition to being a relatively simple movement [45].…”
Section: Discussionmentioning
confidence: 99%
“…Warming aims at improving nerve conduction, allied to an increase in temperature [25,26]. The specific warm-up has been shown to improve strength [27,28,29], however, variations in the type of warm-up can be harmful [30]. Currently, there is no consensus between the effect of different types of warm-ups [29,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Warm-ups aim to improve nerve conduction, combined with an increase in temperature [2][3][4]. Specific warm-ups have been shown to improve strength [5][6][7], however, variations in the type of warm-up can be harmful [8].…”
Section: Introductionmentioning
confidence: 99%